The Impact of Entrepreneurial Orientation on Sustainable Marketing in Hayel Saeed Anam Group - Faiza Ahmed; Abeer Jameel Thabet; Ejlal Waleed Al-Hamedi (مجلة الدراسات الاجتماعية)
This study examines the impact of entrepreneurial orientation on sustainable marketing within Hayel Saeed Anam Group. Using descriptive and analytical methods, the research targeted senior managers and department heads in Sana'a and Aden. Data was collected via paper and electronic questionnaires, divided into two sections: personal and functional characteristics of respondents, and study variables (entrepreneurial orientation and sustainable marketing). Out of 96 distributed questionnaires, all were suitable for statistical analysis. Key findings revealed that Hayel Saeed Anam Group demonstrates a high level of entrepreneurial orientation and strongly adopts sustainable marketing practices. The study confirmed a statistically significant relationship between entrepreneurial orientation and sustainable marketing. Additionally, responses varied significantly based on personal and functional characteristics such as gender, age, education, job title, and years of service. The study recommends that the group emphasizes entrepreneurial orientation across its five dimensions—creativity, proactivity, risk-taking, independence, and competitive aggressiveness—and further integrates sustainable marketing into its strategies to enhance its market position and long-term sustainability.